Local Homoepitaxial Growth in Sputtered NiO Thin Films: An Effective Approach to Tune the Crystallization, Preferred Growth Orientation, and Electrical Properties. Issue 9 (28th June 2018) - Wang, Yong; Ghanbaja, Jaafar; Soldera, Flavio; Boulet, Pascal; Horwat, David; Mücklich, Frank; Pierson, Jean‐Francois
Abstract : We report the local homoepitaxial growth of NiO thin films with simultaneously tunable crystallization, preferred growth orientation, and electrical properties by reactive sputtering. Using a seed layer with 〈 100 〉 fiber texture previously deposited on glass and silicon substrates, the room temperature growth of highly 〈 100 〉 ‐oriented NiO thin films with good crystallization has been achieved. Microstructure analyses evidence that the columns of the top layer are homoepitaxially grown on the columns of seed one. The resistivity of 〈 100 〉 ‐oriented homoepitaxial layer is lower than the seed one and higher than that of single layer of multiple orientations deposited with the same condition. Abstract : Local epitaxial growth is evidenced during the deposition of NiO by reactive sputtering. Using this effect, the film preferred orientation becomes independent of the deposition conditions and the functional properties of the films can be improved without intentionally heating and biasing the substrates. This approach is also expected to be extended to other thin films.